A review on biomass-derived activated carbon as electrode materials for energy storage supercapacitors. (30th November 2022) - Luo, Lu; Lan, Yuling; Zhang, Qianqian; Deng, Jianping; Luo, Lingcong; Zeng, Qinzhi; Gao, Haili; Zhao, Weigang
Abstract: Due to its low cost, diverse sources, and sustainable benefits, biomass-derived activated carbon has gotten much attention recently. An overview of the activation methods and mechanisms used in various biomass activated carbons is presented in this article, as well as a review of the recent progress made in the application of biomass activated carbons in electrochemical supercapacitors during the past three years. The mechanisms and impacts of various activation treatment procedures on the apparent morphology and pore structure of activated carbon materials are briefly discussed. In addition, this article also summarizes the effects of different factors on the performance of supercapacitors, including the texture structure and pore size distribution, the chemical property of heteroatoms doping, the degree of graphitization, and different types of electrolytes and activated carbon-based composites electrodes. The current state of research on biomass activated carbon in the field of the supercapacitor, as well as the future development prospects and challenges in promoting the application of biomass activated carbons in a wide range of fields, were summarized, and useful enlightenment for further development and exploitation of biomass was provided. Graphical abstract: Unlabelled Image Highlights: Biomass-based ACs can be produced by chemical or physical activation. Electrochemical performance is most affected by pore structure. Electrochemical performance can be significantly improved by heteroatoms doping. The future of activated carbon is to combine with inorganic and organic materials.